2015
DOI: 10.1101/016477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eight thousand years of natural selection in Europe

Abstract: The arrival of farming in Europe around 8,500 years ago necessitated adaptation to new environments, pathogens, diets, and social organizations. While indirect evidence of adaptation can be detected in patterns of genetic variation in present-day people, ancient DNA makes it possible to witness selection directly by analyzing samples from populations before, during and after adaptation events. Here we report the first genome-wide scan for selection using ancient DNA, capitalizing on the largest genome-wide dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 91 publications
(26 reference statements)
4
79
0
3
Order By: Relevance
“…There is also evidence that these genes underwent selection more recently in the history of Europeans (Mathieson et al 2015), which could suggest an extended period of selection-perhaps influenced by migrations between Asia and Europe-or repeated selective events at the same locus.…”
Section: Selection In Eurasiansmentioning
confidence: 99%
“…There is also evidence that these genes underwent selection more recently in the history of Europeans (Mathieson et al 2015), which could suggest an extended period of selection-perhaps influenced by migrations between Asia and Europe-or repeated selective events at the same locus.…”
Section: Selection In Eurasiansmentioning
confidence: 99%
“…BC or later. Genetic (3) and isotope data (4) have revealed that demographic movements brought these Neolithic novelties from the Near East into Europe through the process by which scarce Mesolithic foragers were either quickly replaced or assimilated into Neolithic lifeways. Isotope analyses have also suggested that Mesolithic diets were largely based on terrestrial, marine, or riverine protein-rich resources (5-7) with scanty evidence for the consumption of plants (8).…”
mentioning
confidence: 99%
“…The Khvalynsk culture contains mitochondrial haplotype U5a (together with U4 and H) (9). If the migrants moved via the mentioned territories, the found subclades of mt-DNA C in Mesolithic-Neolithic remains could be the evidence (as they preserved in Yuzhniy Oleni Ostrov and Dnieper-Donetsk area), but there are no such findings.…”
mentioning
confidence: 96%